'Carcinogens in a puff': smoking in Hong Kong movies. Issue 6 (18th September 2010) - Ho, Sai-Yin; Wang, Man-Ping; Lai, Hak-Kan; Hedley, Anthony J; Lam, Tai-Hing
Abstract : Smoking scenes in movies, exploited by the tobacco industry to circumvent advertisement bans, are linked to adolescent smoking. Recently, a Hong Kong romantic comedy Love in a puff put smoking at centre stage, with numerous smoking scenes and words that glamourise smoking. Although WHO has issued guidelines on reducing the exposure of children to smoking in movies, none is adopted in Hong Kong. Comprehensive tobacco control strategies are urgently needed to protect young people in Hong Kong from cigarette promotion in movies.